Lumped damage mechanics as a diagnosis tool of reinforced concrete structures in service: case studies of a former bridge arch and a balcony slab - Rafael Nunes da Cunha; Camila de Sousa Vieira; David Leonardo Nascimento de Figueiredo Amorim (Fracture and Structural Integrity)
Reinforced concrete structures may need repair in order to ensure the designed durability. The assessment of the structural condition usually is made in loco, but sometimes numerical analyses are required as a low cost and effective preliminary diagnosis. Lumped damage mechanics (LDM) may be used as an alternative diagnosis procedure. In LDM approaches for reinforced concrete structures, the concrete cracking in modelled by a damage variable and the reinforcement yielding is represented by plastic deformations. Therefore, this paper presents LDM as a diagnosis tool to analyse actual structures. Then, the procedure is applied in two case studies. The first one is a former bridge arch tested in laboratory. Such bridge was deactivated after almost three decades in service and some damage were observable. The second case study deals with a reinforced concrete balcony that collapsed after fifteen years of service. In the moment of collapse, only the dead load was acting in the balcony. The results show that LDM numerical response of those structures are quite close to laboratory observations, for the former bridge arch, and to in loco measurements, for the balcony. In this sense, according to the analysed structures, LDM may be used as a diagnosis tool